Merumuskan Etika Politik Kristen dalam Era Gangguan Terorisme di Indonesia - Paulus Eko Kristianto (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2019)
Abstract. Disruption of terrorism was a serious thing that threatens the life of nationalism in Indonesia. This disorder must be responded quickly and precisely as soon as possible. This article aimed to formulate one of the steps that could be taken, namely by building relevant Christian political ethics. The method used was descriptive analysis of various related literature that addresses this theme. In conclusion, Christian political ethics that have to be practiced by Christians is to develop an open understanding of "the other", including developing neighbouring theology.Abstrak. Gangguan terorisme merupakan hal yang serius mengancam kehidupan berbangsa di Indonesia. Gangguan ini harus direspon dengan cepat dan tepat sesegera mungkin. Artikel ini bertujuan untuk merumuskan salah satu langkah yang bisa dilakukan yakni dengan membangun etika politik Kristen yang relevan. Metode yang digunakan adalah deskriptif analisis pada berbagai literaur terkait yang membahas tema ini. Kesimpulannya, etika politik Kristen yang harus diamalkan orang Kristen yaitu membangun pemahaman terbuka terhadap “sang liyan”, termasuk mengembangkan teologi pertetanggaan.